Analysis of Protein Intake Among Female Adolescents in Tasikmalaya City - Rizka Fikrinnisa; Lilik Hidayanti; Luh Desi Puspareni (Sarana Ilmu Indonesia (Salnesia), 2026)
Adequate protein quantity and quality are vital to support the rapid physical growth, development, and specific nutritional needs of adolescent girls. This study aimed to analyze protein intake in adolescent girls. This was an observational study with a cross-sectional design. The subjects were 514 female students from 10 public junior high schools in Tasikmalaya City who were selected using proportional random sampling. Protein intake was measured using a 2 x 24-hour non-consecutive food recall method. Total protein intake data (g) were separated into animal protein intake and vegetable protein intake. Demographic factors, eating habits, and behavior of the subjects were measured using a structured questionnaire. Analysis used the Spearman Rank Test and the Mann Whitney Test for non-normally distributed data. The results that showed a relationship with total protein intake were age (p = 0.013), father's education (p = 0.005), mother's education (p = 0.001), father's occupation (p < 0.001), and snacking habits (p = 0.008). Factors associated with animal protein intake were maternal education (p = 0.03), paternal occupation (p = 0.003), and maternal occupation (p = 0.028). Meal skipping was associated with total protein intake (p = 0.004) and vegetable protein intake (p = 0.016). Breakfast habits were associated with animal protein intake (p = 0.048). This provided a basis for designing appropriate nutrition programs, including education about healthy food choices and the importance of nutrient balance in the daily diet of adolescent girls.